2003
DOI: 10.1182/blood-2002-08-2525
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of TRAIL-induced apoptosis in primary effusion lymphoma through azidothymidine-mediated inhibition of NF-κB

Abstract: The survival of viral mediated lymphomas depends upon constitutive nuclear factor kappa B (NF-B) activity. AIDS-related human herpesvirus type 8-associated primary effusion lymphoma (PEL) responds poorly to chemotherapy and is almost invariably fatal. We have previously demonstrated that the antiviral combination of interferon alpha (IFN-␣) and azidothymidine (AZT) induces apoptosis in PEL cell lines. We therefore used these agents as therapy for an AIDS patient with PEL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 38 publications
2
60
0
1
Order By: Relevance
“…Several in vitro studies have shown that inhibition of the NF-kB pathway could induce apoptosis in myeloma, lymphoma and leukemia patient cells and may be beneficial for the treatment of these malignancies. [150][151][152][153][154] Of particular interest are the clinical trials using the proteasome inhibitor PS-341 (VELCADE/bortezomib). Proteasome inhibition downregulates the NF-kB pathway and decreases the expression of IAPs and other antiapoptotic genes.…”
Section: Iaps As Targets For Cancer Therapymentioning
confidence: 99%
“…Several in vitro studies have shown that inhibition of the NF-kB pathway could induce apoptosis in myeloma, lymphoma and leukemia patient cells and may be beneficial for the treatment of these malignancies. [150][151][152][153][154] Of particular interest are the clinical trials using the proteasome inhibitor PS-341 (VELCADE/bortezomib). Proteasome inhibition downregulates the NF-kB pathway and decreases the expression of IAPs and other antiapoptotic genes.…”
Section: Iaps As Targets For Cancer Therapymentioning
confidence: 99%
“…2 In fact, drugs that inhibit NF-kB activation have exhibited considerable activity against PELs both in vitro and in vivo. [1][2][3] In addition, inhibition of NF-kB sensitizes PEL cells to tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis. 3 Recently, the proteasome inhibitor bortezomib (formerly PS-341) has demonstrated potent cytotoxicity across a wide variety of hematologic malignancies and solid tumors and received approval by the Food and Drug Administration (FDA) for the treatment of refractory multiple myeloma, where it has an acceptable toxicity profile.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In addition, inhibition of NF-kB sensitizes PEL cells to tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis. 3 Recently, the proteasome inhibitor bortezomib (formerly PS-341) has demonstrated potent cytotoxicity across a wide variety of hematologic malignancies and solid tumors and received approval by the Food and Drug Administration (FDA) for the treatment of refractory multiple myeloma, where it has an acceptable toxicity profile. [4][5][6] By inhibiting the proteasome, which degrades proteins that are marked by ubiquitination, bortezomib modulates the cellular concentrations of hundreds of proteins that are involved in a wide variety of functions, including cell cycle progression, signal transduction, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…As we have recently shown, LV-TRAIL particles contain the membrane-bound 42 kDa form of TRAIL, which is expressed in the 293 T producer cells upon transfection. 24 Thus, the residual apoptosis may be due to the TRAIL protein present in the viral particles, or due to the ability of AZT to sensitize for TRAIL-induced apoptosis, 32 or a combination of both. As both constructs express the marker gene GFP, we could measure the transduction efficiency of each construct by FACS analysis of GFP expression ( Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…This is in line with previous observations demonstrating that enveloped viruses with CD95-L or TRAIL transgenes carry these proteins on their surface, as a result from protein expression in the packaging cells. 24,37 Unfortunately, our attempt to further characterize this transduction-independent induction of cell death by AZT, an inhibitor of reverse transcriptase, was hampered, as this substance sensitizes for TRAIL-induced apoptosis (own observation, compare also Ghosh et al 32 ). Also, cells treated with AZT or ddC at concentrations required for inhibition of transduction underwent growth arrest after 5-7 days of culture (own data, not shown).…”
Section: Discussionmentioning
confidence: 99%